A new endangered species of Chusquea (Poaceae: Bambusoideae) from the Acatlán volcano in central Veracruz, Mexico, and keys to the Mexican Chusquea species - Ruiz-Sanchez, Eduardo; Mejía-Saulés, Teresa; Clark, Lynn G. (Phytotaxa, 2014)
Mexico has 19 species of the diverse neotropical bamboo genus Chusquea, 15 of them growing in Neotropical cloud forests, with ten of those 19 species endemic to Mexico. The cloud forest is one of the most threatened types of vegetation in Mexico. Based on fieldwork at the Acatlán volcano in the Mexican state of Veracruz and morphological analysis of live and herbarium specimens, here we describe and illustrate a new endemic and endangered Chusquea species. Chusquea enigmatica is a narrow endemic to volcano Acatlán and has an unusual reduction of vegetative morphological characters. Chusquea enigmatica is compared with C. glauca, C. muelleri and C. repens, from which it can be separated by its delicate and erect culms, extravaginal or intravaginal branching pattern and reduction of bud size. Chusquea enigmatica only inhabits the rim of the volcano Acatlán in cloud forest dominated by Fagus grandifolia in small patches, for which reason we propose to include this species in the IUCN red list under the “endangered” category of protection. Keys to the currently recognized species of Chusquea in Mexico are also provided.